The Application Of Magnesium Ferrite Photocatalyst For Photo Treatment Of Methylene Blue - Kong, Zi Ying; Wong, Nyap Xiang; Cheng, C. K.; Khan, Maksudur R. (2014)
The current work reports on the use of photocatalysis technique to decompose Methylene Blue (MB), an industrial-grade dye. Visible light-activated MgFe2O4 photocatalyst was synthesized using solid-solid method in a Mg:Fe ratio of 1:2 by mol. The photocatalyst was characterized using X-ray diffraction method (XRD) and field-emission scanning electron microscopy/energy dispersive x-ray analysis (FESEM-EDX). The results indicate that the solid catalyst exhibited high crystallinity with MgFe2O4 as the main compound. In addition, it has macropores structure with uniform formation of particles as suggested by FESEM images. Significantly, the performance and kinetics of photo-degradation of 20 ppm MB solution were studied over different catalyst loadings viz. 0.2, 0.5, 1.0, 1.5 and 2.0 g/L in the presence of xenon lamp (250 W). Kinetic modelling results indicate that the photodegradation followed the zero-order rate of reaction. Moreover, MB degradation seems to increase incrementally up to the 1.5 g/L beyond which the performance has deteriorated.